HOSPITAL EMPLOYEE PERFORMANCE ANALYSIS BASED ON QUALITY, QUANTITY, TIMELINESS, AND WORK EFFECTIVENESS DIMENSIONS: A CASE STUDY - Fadhilla Syahputra, Zakka; Mufarrid, Hafidh Arum; Mochklas, Mochamad (Universitas Muhammadiyah Surakarta, 2026)
Optimal performance reflects individual effectiveness in task execution and directly contributes to the quality of services provided. This study aims to analyze how quality of work, quantity of output, timeliness, and work effectiveness influence employee performance at Griya Waluya Hospital Ponorogo in 2024. A quantitative correlational method was used, focusing on collecting and analyzing numerical data to determine the relationships between variables. The population includes all employees of the hospital 400 individuals, with 80 participants selected using quota sampling. Data were obtained through questionnaires, direct observations, and document analysis. Multiple linear regression analysis was conducted using SPSS software. The findings reveal that all examined dimensions work quality, workload, punctuality, and work efficiency significantly impact overall employee performance. These results suggest that improvements in each dimension can enhance staff performance outcomes. Therefore, hospital management is encouraged to continuously monitor and strengthen these aspects through targeted training, performance evaluations, and development programs aligned with key performance indicators (KPIs). This study contributes to performance management practices by emphasizing the importance of a balanced focus on various performance dimensions in health service institutions.